(untitled) (Annals of Medical Research, 2021)
Aim: There is no examination to determine the exact diagnosis of parathyroid cancer before surgery. The aim of this study was to discuss our surgical experience and the intraoperative findings suggestive of cancer, in parathyroid cancers operated with the diagnosis of primary hyperparathyroidism.Material and Methods: Six patients with parathyroid cancer who were operated on between May 2012 and January 2017, in the Department of General Surgery, xxx were included in the study. Age, sex, complaints of the patients, calcium and parathormone values, imaging methods for localization, intraoperative findings from surgical notes were evaluated retrospectively.Results: Of the patients, 4 were females and 2 were males. The mean age was 61.6+7.28 (50-71). While the lesion was spotted incidentally in three patients, swelling in the neck, back and hip pain, pancreatitis were other reasons for admission. The mean calcium levels were 13.05+1.86 (10.5-15.7) mg/dL, mean parathormone values were 937.4+756.9 (370-1814) pg/ml. Ultrasonography (USG) and parathyroid scintigraphy were performed to all patients. Thyroid scintigraphy was additionally performed on one patient for hyperthyroidism and then FNAB was performed. This patient was operated on with suspected thyroid cancer. In intraoperative evaluation, all of the lesions were firm, adherent to the thyroid capsule and surrounding tissues. One patient had inferior laryngeal nerve invasion. In frozen examination, four patients with suspected parathyroid cancer was specified. Three patients had a lobectomy and 2 patients had en bloc lesion resection with total thyroidectomy. Lesion excision was performed in one patient. After final pathology results, re-operation was suggested, however the patient did not accept.Conclusion: The definitive diagnosis in parathyroid cancer is made by postoperative pathological examination. In cases of primary hyperparathyroidism, in case of intravesical invasion of the thyroid capsule and surrounding tissues during intraoperative examination, parathyroid cancer should be suspected. In case of suspicious findings in frozen examination and intraoperative findings, the surgical plan may be changed and the necessity of secondary surgery can be eliminated.Keywords: Parathyroidcarcinoma; thyroidectomy, hypercalcemia.